University students with attention deficit hyperactivity disorder (ADHD): a consensus statement from the UK Adult ADHD Network (UKAAN) - Jane A. Sedgwick-Müller; Ulrich Müller-Sedgwick; Marios Adamou; Marco Catani; Rebecca Champ; Gísli Gudjónsson; Dietmar Hank; Mark Pitts; Susan Young; Philip Asherson (BMC Psychiatry, 2022)
Abstract Background Attention deficit hyperactivity disorder (ADHD) is associated with poor educational outcomes that can have long-term negative effects on the mental health, wellbeing, and socio-economic outcomes of university students. Mental health provision for university students with ADHD is often inadequate due to long waiting times for access to diagnosis and treatment in specialist National Health Service (NHS) clinics. ADHD is a hidden and marginalised disability, and within higher education in the UK, the categorisation of ADHD as a specific learning difference (or difficulty) may be contributing to this. Aims This consensus aims to provide an informed understanding of the impact of ADHD on the educational (or academic) outcomes of university students and highlight an urgent need for timely access to treatment and management. Methods The UK Adult ADHD Network (UKAAN) convened a meeting of practitioners and experts from England, Wales, and Scotland, to discuss issues that university students with ADHD can experience or present with during their programme of studies and how best to address them. A report on the collective analysis, evaluation, and opinions of the expert panel and published literature about the impact of ADHD on the educational outcomes of university students is presented. Results A consensus was reached that offers expert advice, practical guidance, and recommendations to support the medical, education, and disability practitioners working with university students with ADHD. Conclusions Practical advice, guidance, and recommendations based on expert consensus can inform the identification of ADHD in university students, personalised interventions, and educational support, as well as contribute to existing research in this topic area. There is a need to move away from prevailing notions within higher education about ADHD being a specific learning difference (or difficulty) and attend to the urgent need for university students with ADHD to have timely access to treatment and support. A multimodal approach can be adapted to support university students with ADHD. This approach would view timely access to treatment, including reasonable adjustments and educational support, as having a positive impact on the academic performance and achievement of university students with ADHD.